G177 A Single-Centre Experience of Central Venous Lines in Paediatric Haematology/Oncology Patients Over Five Years. (4th June 2013) - Toh, RYM; Mackay, H; Isaac, A; Keys, C; Edgar, AB; Wallace, WH
Abstract : Background and Aims: Safe central venous access is required for the management of paediatric patients with solid and haematological malignancies. The objective of this study was to retrospectively review central venous lines (CVL) experience in a single centre over a five-year period between 2007 and 2012 to determine the prevalence of line-associated complications and predisposing factors for premature line removal. Methods: All patients had either a single or double lumen external catheter (Hickman) or Portacath inserted. The choice of catheter for each patient is individualised. The Lothian Surgical Audit System, TRAK, iLAB and case notes were reviewed for patient demographics, surgical details of line insertion, line-associated complications and reasons for removal of line. Results: 140 patients underwent 213 line insertions, with 80 (57.1%) patients experiencing a line-associated complication (total number of episodes n = 145). Proven infection was the most common complication (77 episodes, 53.1%), followed by blockages (43 episodes, 29.7%), dislodgement (12 episodes, 8.3%), fracture (7 episodes, 4.8%), kinking (2 episodes, 1.4%), migration (1 episode, 0.7%), extravasation (1 episode, 0.7%), atelectasis (1 episode, 0.7%) and skin breakdown over Portacath (1 episode, 0.7%). The median (range) number of catheter days for single CVL was 309.5 days (range 9–1357 days) for Portacaths and 82.5 (15–218 days) for Hickman lines. The median catheter duration for double CVL was 198.5 (1–582) days and 112 (0–882) days for Portacaths and Hickman lines respectively. Single Hickman lines had the highest rate of premature removal (42.9%), followed by double Hickman lines (42.6%), double Portacaths (35.7%) and single Portacaths (22.9%). The presence of severe thrombocytopenia (<50 × 109/L) and severe neutropenia (<0.5 × 109/L) at insertion were associated with higher rates of premature removal due to infection (20.0% and 19.6% respectively), compared with CVL with platelet count ≥50 × 109/L and neutrophils ≥1.0 × 109/L (18.3% and 18.2% respectively). Conclusion: Single Portacaths are the longest surviving central venous lines. The presence of thrombocytopenia and/or neutropenia at the time of insertion may be associated with an increased risk of line sepsis and premature removal.